Necessary and Sufficient Conditions on Negative Imaginariness for Interval SISO Transfer Functions and Their Interconnection - Liu, Mei; Lam, James; Lin, Hong; Jing, Xingjian (IEEE transactions on automatic control, 2020)
This article is concerned with the study of the negative imaginariness of interval transfer functions. Necessary and sufficient conditions for (strictly) negative imaginary interval transfer functions subject to parameter uncertainty are first derived based on Kharitonov's theorem. Then, certain properties of the interconnection system with negative imaginary interval transfer functions are analyzed. Finally, an example is provided to illustrate the main results of the article.